The Prediction of Bankruptcy With Altman Z-Score and Springate S-Score Models In Sharia Banks Period 2012-2017 - Hana Tamara Putri (J-MAS (Jurnal Manajemen dan Sains), 2019)
The Background of this research is to know and to analyze the prediction of company bankruptcy of BUMN Syariah Banks in BEI periods 2012-2017 which focuses object are three companies which have all criteria in analysis by method Z-score Altman and S-Score Springate. As we know, the goal of company is not being bankrupt so that the company needed a method to predict the bankruptcy as soon as possible. This reserch uses Z-Score Altman and S-Score Springate, this methods used to analize financial statements. Goals of this research is to know the potential of bankruptcy, rate of bankruptcy, and insolvensy ranking  of BUMN Syariah Banks in BEI periods 2012-2017. Three companies taken as object are Bank Mandiri Syariah, Bank BNI Syariah and Bank BRI Syariah, analyze by using financial statements by the year 2012 to 2070 to find values of variables and then calculated the value of each variable into Altman’s Formula and Springate’s Formula to produce the score.